Serological and molecular diagnostic tests for canine visceral leishmaniasis in Brazilian endemic area: one out of five seronegative dogs are infected - Lopes, E. G.; Seva, A. P.; Ferreira, F.; Nunes, C. M. [UNESP]; Keid, L. B.; Hiramoto, R. M.; Ferreira, H. L.; Oliveira, T. M. F. S.; Bigotto, M. F. D.; Galvis-Ovallos, F.; Galati, E. A. B.; Soares, R. M. (Cambridge Univ Press, 2017)
Euthanasia of infected dogs is one of the measures adopted in Brazil to control visceral leishmaniasis (VL) in endemic areas. To detect infected dogs, animals are screened with the rapid test DPP (R) Visceral Canine Leishmaniasis for detection of antibodies against K26/K39 fusion antigens of amastigotes (DPP). DPP-positives are confirmed with an immunoenzymatic assay probing soluble antigens of promastigotes (ELISA), while DPP-negatives are considered free of infection. Here, 975 dogs from an endemic region were surveyed by using DPP, ELISA and real-time PCR (qPCR) for the diagnosis of VL. When DPP-negative dogs were tested by qPCR applied in blood and lymph node aspirates, 174/887 (19.6%) were positive in at least one sample. In a second sampling using 115 cases, the DPP-negative dogs were tested by qPCR in blood, lymph node and conjunctival swab samples, and 36/79 (45.6%) were positive in at least one sample. Low-to-moderate pairwise agreement was observed between all possible pair of tests. In conclusion, the official diagnosis of VL in dogs in Brazilian endemic areas failed to accuse an expressive number of infected animals and the impact of the low accuracy of serological tests in the success of euthanasia-based measure for VL control need to be assessed.
Keywords: Dogs; PCR; serodiagnosis; visceral leishmaniasis